Female gender and differences in outcome after isolated coronary artery bypass graft surgery: does age play a role? - Arif, Rawa; Farag, Mina; Gertner, Victor; Szabó, Gábor; Weymann, Alexander; Veres, Gábor; Ruhparwar, Arjang; Bekeredjian, Raffi; Bruckner, Thomas; Karck, Matthias; Kallenbach, Klaus; Beller, Carsten J. (PLOS ONE, 2016)
Introduction Female gender is a known risk factor for early and late mortality after coronary artery bypass graft surgery (CABG). Higher age of women at operation may influence outcome, since age per se is also an important risk factor. The purpose of our study was to analyze possible gender differences in outcome after isolated CABG in different age groups to delineate the impact of female gender and age. Methods All patients over 60 years of age undergoing isolated CABG at our department during 2001 and 2011 were included and categorized by age into sexagenarians (2266, 16.6% women), septuagenarians (2332, 25.4% women) and octogenarians (374, 32% women) and assessed by gender for 30-day and 180-day mortality. Results Thirty-day mortality was significantly higher in women only amongst septuagenarians (7.1 vs. 4.7%, p = 0.033). Same differences apply for 180-day mortality (12.3 vs. 8.2%, p = 0.033) and estimated one-year survival (81.6 ± 4.2 vs. 86.9 ± 2.2%, p = 0.001). Predictive factors for 30-day mortality of septuagenarian were logistic EuroSCORE (ES) (p = 0.003), perioperative myocardial infarction (MI) (p<0.001), pneumonia (p<0.001), abnormal LV-function (p<0.04) and use of LIMA graft (p<0.001), but not female gender. However, female gender was found to be an independent predictor for 180-day mortality (HR 1.632, p = 0.001) in addition to ES, use of LIMA graft, perioperative MI, pneumonia and abnormal LV function (HR 1.013, p = 0.004; HR 0.523, p<0.001; HR 2.710, p<0.001; HR 3.238, p<0.001; HR 2.013, p<0.001). Conclusion Women have a higher observed probability of early death after CABG in septuagenarians. However, female gender was not found to be an independent risk factor for 30-day, but for 180-day survival. Therefore, reduction of high impact risk factors such as perioperative MI and enhancement of LIMA use should be future goals. In view of our findings, decision for surgical revascularization should not be based on gender.
Gesehen am 20.11.2019